Supplement usage and development of Clarias gariepinus fed to four different commercial feeds - Osinbajo Meshack Abiodun (Advances in Aquaculture and Fisheries Management, 2015)
Several studies had been conducted on the nutritional requirements of African catfish, Clarias gariepinus. Nevertheless, currently there is a gap about the gross composition of feed ingredients required for formulation of commercial feeds. The aims of this feeding trial were to investigate whether fish fed four different commercial feeds have a significant growth rate and nutrient utilization. A total of 120 fish samples were stocked for a triplicate feeding trial (10 fish for each replication) in 4 separated tanks with 4 different feeds: Euro, Melick, Coppens and Durante (T1), (T2), (T3) and (T4) respectively. During all the trial, the water quality and growth parameters were determined according to standard methods and no significant differences were found among the water quality parameters determined. The mean weight gain (MWG) and specific growth rate of T3 were significantly higher than those of other treatments. Statistics showed that protein efficiency ratio (PER) of T3 was significantly higher than other treatments. Contrary to the above trend, the feed conversion ratio (FCR) of T2 was significantly higher than other treatments. According to the results of this study, fish fed with Coppens feed showed a significant growth rate and nutrient utilization.